Infants' Understanding of Information Transmission in the Context of Communication Involving Multiple Agents. (17th September 2015) - He, Jie; Jin, Xinyi; Li, Zhuyun; Zheng, Lei; Sun, Zhongqiang; Zhang, Meng; Shen, Mowei
Abstract : This study explored whether infants understand information transmission in a third‐party communication context involving multiple agents. Infants aged 12 and 15 months were habituated to two agents pursuing two different objects and then tested with one agent (the communicator) interacting with a new agent (the recipient), whereas the other agent (the noncommunicator) did not interact with anyone. Results showed that 15‐month‐olds looked for longer when the recipient reached toward the preferred object of the noncommunicator in contrast to that of the communicator, suggesting that they recognized information transmitted from the communicator (versus the noncommunicator) to the recipient. Furthermore, the information was perceived as being specifically transmitted between agents, and this inference was not driven by the low‐level perceptual factors of the communicator or the communication itself. However, 12‐month‐old infants did not show an understanding of transmission between the agents. The selective understanding of information transmitted among multiple agents, and the critical role of agency in such understanding are discussed.